Antenatal pertussis vaccination: Are we implementing best evidence into practice?. (5th October 2016) - Krishnaswamy, Sushena; Wallace, Euan; Buttery, Jim; Giles, Michelle
Abstract : Maternal immunisation is the most effective strategy to reduce infant morbidity and mortality from pertussis infection, and is now standard of care in many countries, including Australia. However, uptake cannot be guaranteed unless the barriers to implementing programs locally are understood. Education and resources for antenatal care providers, embedding vaccination within antenatal care, and provision of culturally appropriate information for pregnant women are integral to a successful antenatal vaccination program.